2011
DOI: 10.1186/1475-2859-10-56
|View full text |Cite
|
Sign up to set email alerts
|

High yield expression in a recombinant E. coli of a codon optimized chicken anemia virus capsid protein VP1 useful for vaccine development

Abstract: BackgroundChicken anemia virus (CAV), the causative agent chicken anemia, is the only member of the genus Gyrovirus of the Circoviridae family. CAV is an immune suppressive virus and causes anemia, lymph organ atrophy and immunodeficiency. The production and biochemical characterization of VP1 protein and its use in a subunit vaccine or as part of a diagnostic kit would be useful to CAV infection prevention.ResultsSignificantly increased expression of the recombinant full-length VP1 capsid protein from chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Previous studies have shown that the N-terminal of the VP1 protein is highly rich in arginine residues and has been proposed to be cytotoxic in an E. coli expression system (Lai et al, 2013;Lee et al, 2011). Our results show that N129 deleted rVP-1 can be expressed in an E. coli system successfully.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous studies have shown that the N-terminal of the VP1 protein is highly rich in arginine residues and has been proposed to be cytotoxic in an E. coli expression system (Lai et al, 2013;Lee et al, 2011). Our results show that N129 deleted rVP-1 can be expressed in an E. coli system successfully.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown that the N-terminal of the VP1 protein is highly rich in arginine residues, and it has been proposed to be cytotoxic in an Escherichia coli expression system (Lai et al, 2013;Pallister et al, 1994). The first 129 N-terminus-deleted VP1 protein (VP1Nd129) can successfully express large amounts of the protein in prokaryotic cells and can be recognized by CAVpositive chicken serum (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, one possibility is that protein solubility was improved [19]. Similarly, in our previous study, the addition of a GST tag to the CAV VP1 protein also improved expression in E. coli significantly compared to a His × 6 tag [13]. Thus some fusion tags would seem to be able to help improve the solubility of E. coli expressed proteins more than other tags; this occurs perhaps by promoting the correct folding of their selected fusion partner [13,19].…”
Section: Discussionmentioning
confidence: 85%
“…Multiple tags can be added together in different combination for a particular protein to get better result on these issues [7]. Various studies report high yield target protein expression with Maltose binding protein (MBP) [19], Glutathione-S transferase (GST) [20], Thioredoxin fusion (TRX) [21], Hexahistidine His6-Tag [19,22], Small ubiquitinmodifier fusion (SUMO) [21], N-utilizing substance A (NusA), Protein S tag (PrS2) [18], Solubility-enhancing tag (SET) [23], Disulfide bond C (DsbC), Seventeen kilodalton protein (Skp), Phage T7 protein kinase (T7PK), Protein G B1 domain (GB1), Protein A IgG ZZ repeat domain (ZZ) [24], histidine tagged Ubiquitin (Ub) fusion and histidine tagged deubiquitylating enzyme (DUB) fusion [25]. Recent studies propose the Outer membrane protein A (OmpA), Outer membrane protein F (OmpF) and Osmotically inducible protein Y (OsmY) as fusion partners secreting protein into the growth medium of E. coli depending on culture conditions via periplasm secretion.…”
Section: Co-expression With Fusion/solubility Tagmentioning
confidence: 99%